Лепная керамика из зольника у горы Митридат - Власов, В.П. (Материалы по археологии, истории и этнографии Таврии, 2008)
Осенью 2002 г. экспедиция Крымского отделения Института востоковедения НАН Украины, возглавляемая А.И. Айбабиным, провела охранные раскопки в зоне ведения строительных работ по ул. Ленина в г. Керчи. На отведенном под застройку участке, примыкавшем к подножию северного склона горы Митридат, расколом ллощадью около 150 м^ были выявлены зольник, а также каменная постройка, составлявшие, по мнению их исследователей, единый культовый комплекс. The article continues a series of publications of finds from the burnt mound at the foothill of the mountain of Mithradates and is devoted to the analysis of hand-made ceramics. The burnt mound consists of two stratigraphic and chronological horizons; the lower of which got a conditional name «Zolnik 1» (burnt mound) and the upper one - «Zolnik 2». Hand-made ceramics found in the burnt mounds does not occupy a considerable place among other kinds of pottery and accounts 1330 instances (100%). It is divided almost in two equal parts between investigated horizons: 47.75% (635 instances) have provenance from Zolnik 1 and 52.25% (695 instances) - from upper Zolnik 2.